PENYUSUNAN LAPORAN KEUANGAN UD. AZHARI BERDASARKAN SAK EMKM - Aminy, Muhammad Habibullah; M. habiburrahman (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2023)
An entity requires financial reports as information on financial position and to measure the financial performance of its business as well as a basis for making financial decisions. The low awareness of UMKM actors to prepare standardized financial reports causes business actors difficulties in developing their business and applying for capital to creditors, in this case banks. This study aims to apply financial reporting based on SAK EMKM standards to UD UMKM. Azhari. The type of research used is quantitative research with a case study approach. The results of research at UD. Azhari has not kept records and does not yet have financial reports that are in accordance with SAK EMKM standards. In running their business, owners and employees only keep records of sales transactions, cash receipts and disbursements transactions. In accordance with the results of the research and discussion, the authors carry out the preparation of financial reports on UMKM UD. Azhari complies with SAK EMKM standards. The financial statements prepared consist of a Profit and Loss Report, a Statement of Financial Position and Notes to Financial Statements.